The Effectiveness of Online Learning in Speaking Class at State University of Makassar During Pandemic Covid-19 - Muhammad Zulfikar; Nurdin Noni; Samtidar Samtidar (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2023)
This research aims to determine the effectiveness of online learning in speaking classes at the State University of Makassar using digital technology as a research variable to find out what types of technology can support the online learning process in speaking courses. This research uses qualitative research methods using interviews and questionnaires as research instruments to be able to determine the effectiveness of learning speaking in online learning. Interviews were conducted with several speaking lecturers in the English department. Meanwhile, the questionnaire was given to several students majoring in English at the Faculty of Languages and Literature. Based on the results of the research by using interviews with lecturers as respondents, various answers were found but resulted in the same point, that is the ineffectiveness of learning speaking English in online learning as well as the results of the questionnaire, where the dominant students answered that learning English speaking was not effective using the online learning method.